Case report: A prosthetic valve endocarditis caused by Legionella bozemanae in an immunocompetent patient - Fraz, Mai Sasaki Aanensen; Dahle, Gry; Skaug, Kirsten Margrete; Jarraud, Sophie; Frye, Stephan; Bjørnholt, Jørgen Vildershøj; Nordøy, Ingvild (Frontiers in Medicine, 2022)
Extrapulmonary infections with Legionella species are rare, but important to acknowledge. We report a case of infective endocarditis (IE) with Legionella bozemanae in a 66-year-old immunocompetent man with an aortic homograft. The diagnosis was made by direct 16S rRNA gene amplification from valve material, confirmed by a targeted Legionella-PCR in serum and the detection of L. bozemanae specific antibodies. To our knowledge, this is the first confirmed case of IE with L. bozemanae as causative pathogen. The infected aortic prosthesis was replaced by a homograft, and the patient was successfully treated with levofloxacin and azithromycin for 6 weeks.